2003
DOI: 10.2337/diacare.26.5.1497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Automated Electronic Reminder in Changing the Antiplatelet Drug–Prescribing Behavior Among Italian General Practitioners in Diabetic Patients

Abstract: OBJECTIVE—To evaluate whether an electronic reminder integrated into a routine computer system increases the use of antiplatelet drugs for diabetic patients among Italian general practitioners (GPs). RESEARCH DESIGN AND METHODS—A randomized controlled trial was carried out among 300 GPs and their patients selected from the Health Search Database. Among these, 150 GPs (intervention group) received instructions to activate an electronic reminder plus a letter summarizing the beneficial effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
90
1
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 20 publications
(14 reference statements)
0
90
1
1
Order By: Relevance
“…Despite this, according to our data, X2 additional antihypertensive drugs could be necessary to aim to the target BP recommended for high-CV risk patients; 3 this is a relevant effort for patients, GPs, and National Health Services. Computer-based strategies [21][22] could be a useful tool both to identify the high-risk patients and to remind the GP to increase the antihypertensive therapy (and to check patient compliance).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, according to our data, X2 additional antihypertensive drugs could be necessary to aim to the target BP recommended for high-CV risk patients; 3 this is a relevant effort for patients, GPs, and National Health Services. Computer-based strategies [21][22] could be a useful tool both to identify the high-risk patients and to remind the GP to increase the antihypertensive therapy (and to check patient compliance).…”
Section: Discussionmentioning
confidence: 99%
“…Completeness and accuracy of information are assessed by running a set of queries (quality indicators) used to generate a composite score ranging from 0-1. Only physicians (n=700) reaching a composite quality score.0.7 were included in epidemiologic studies (12,13), and the validity of the data has been previously shown (14)(15)(16).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, we believe that the emphasis should be on changing provider behavior (25,26,(32)(33)(34)(35)(36)(37)(38)(39)(40)43). Our strategy was based on previous surveys that indicated that the residents were familiar with glycemic goals (58) and diabetes medications but often failed to intensify therapy when glucose levels were high (28).…”
Section: A1c Outcomes In the Intervention Site Versus Other Primary Cmentioning
confidence: 99%